A combined-model for uncertain load and optimal configuration of distributed generation in power distribution system - Nallagownden, P. (UK Simulation Society, 2017)
The electric distribution system can be the most stressed part of a power system. Firstly, the electric load is stochastic in nature and fluctuates throughout the day. Secondly, the distribution system previously had one directional power flow but now Distributed Generation (DGs) is being integrated and result in bi-directional power flow. In the context of these challenges, this paper presents a combined-model which handles the uncertain load variations and optimal placement and sizing of DG into the distribution system. The uncertainties in the load are modelled by probability distribution functions (PDF) of load with Hong’s two-point estimation method. The optimal placement and sizing of DG in candidate buses are proposed by particle swarm optimization (PSO) method. The results are compared with analytical approaches and grid search algorithms. © 2017, UK Simulation Society. All rights reserved.